2007
DOI: 10.1590/s0004-282x2007000200031
|View full text |Cite
|
Sign up to set email alerts
|

Oligosymptomatic and giant basilar artery dolichoectasia discovered after a stroke: case report

Abstract: The most frequently diagnosed complication of vertebrobasilar dolichoectasia (VBD) is the compression of structures adjacent to the vertebral and basilar arteries. A giant VBD with only slight compressive symptoms is unusual. In this setting, the diagnosis of VBD may be casually revealed after the occurrence of a posterior circulation stroke, another potential complication. We report a 48-year-old woman who presented a two-month history of continuous buzz and a slight right-sided hearing loss that was followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The authors proposed that direct compression of the XI th and VII th cranial nerves by the dolichoectatic left vertebral artery might be the mechanism responsible for myoclonus in their patient 21 . Campos et al 9 reported a 48-yearold woman who presented a twomonth history of continuous buzz and a slight right-sided hearing loss that was followed by a cerebellar ischemic stroke. Brain CT and MRI revealed a marked compression of the brainstem due to an ectatic, tortuous and partially thrombosed basilar artery.…”
Section: Posterior Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors proposed that direct compression of the XI th and VII th cranial nerves by the dolichoectatic left vertebral artery might be the mechanism responsible for myoclonus in their patient 21 . Campos et al 9 reported a 48-yearold woman who presented a twomonth history of continuous buzz and a slight right-sided hearing loss that was followed by a cerebellar ischemic stroke. Brain CT and MRI revealed a marked compression of the brainstem due to an ectatic, tortuous and partially thrombosed basilar artery.…”
Section: Posterior Circulationmentioning
confidence: 99%
“…Diagnosis was made only after the occurrence of a stroke. According to the authors, the presence of significant atherosclerotic changes and the large basilar artery diameter may indicate a poor outcome 9 . Interestingly, Tsutsumi et al 22 reported a 71-year-old female with basilar and bilateral carotid dolichoectasia manifesting as dysarthria and hemisensory disturbance, which resolved spontaneously within a day.…”
Section: Posterior Circulationmentioning
confidence: 99%
See 1 more Smart Citation